The Role of Vitamin B12 in the Management and Optimization of Treatment in Patients With Degenerative Cervical Myelopathy. Issue 3 (May 2019) - Nouri, Aria; Patel, Kishan; Montejo, Julio; Nasser, Rani; Gimbel, David A.; Sciubba, Daniel M.; Cheng, Joseph S.
Study Design: Narrative review. Objectives: To discuss the relationship between degenerative cervical myelopathy (DCM) and vitamin B12 deficiency. Specifically, it is the aim to outline the rational for future research into assessment and therapeutic optimization of vitamin B12 in the treatment of DCM. Methods: Literature review. Results: DCM is the commonest cause of spinal cord impairment, with an average age of presentation in the sixth decade. Patients at this age have also been reported to have a high prevalence of vitamin B12 deficiency, with estimates of up to 20% in the elderly. Vitamin B12 deficiency can result in subacute combined degeneration of the spinal cord (SACD), and several case reports have pointed to patients with both DCM and SACD. Both SACD and reversible compressive injury due to DCM necessitate remyelination in the spinal cord, a process that requires adequate vitamin B12 levels. Basic science research on nerve crush injuries have shown that vitamin B12 levels are altered after nerve injury and that vitamin B12 along with dexamethasone or nonsteroidal anti-inflammatory drugs can reduce Wallerian degeneration. Furthermore, it has been suggested that a combination of B-vitamins can reduce glutamate-induced neurotoxicity. Conclusions: Given the high prevalence of clinical and subclinical vitamin B12 deficiency in the elderly, the role of vitamin B12 in myelination, and vitamin B12 deficiency as a differential diagnosis of DCM, it is important to investigate what role vitamin B12 levels play in patients with DCM in terms of baseline neurological function and whether optimization of vitamin B12 levels can improve surgical outcome. Furthermore, the routine assessment of vitamin B12 levels in patients considered for DCM surgery should be considered.